ENDOSCOPIC APPEARANCE OF CHRONIC DYSPEPSIA IN RSUP DR.SARDJITO YOGYAKARTA YEAR 2009 - 2010 - , JUANDA HANJAYA; , dr. Neneng Ratnasari, Sp.PD-KGEH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Dyspepsia is the most common problem occurring in all ages. Its estimated between 20% - 45% in general population. Endoscopy act as an early diagnostic test of underlying disease appears in chronic dyspepsia and should be performed in patient with alarm symptoms and patient over 45 years old. Objective: Having endoscopy appearance image storage of chronic dyspepsia patient and analytical differentiation by its sex and age group of patient. Method: The study design was retrospective with analytical descriptive. The subjects of this research were dyspepsia patients who underwent endoscopy in RSUP Dr. Sardjito from January 2009 to December 2010. The instrument used was medical records of patients. Result: Based on the study, there was significant difference in lesion found during endoscopy (p<0.001). The frequent endoscopic lesion were located in gaster 48,5%, followed with combination of esophagus and gaster 17,4%, gaster and duodenum 11% , and normal 11% On the other hand, analytical studies in age classification (18-45 and â¥45 years old) and gender showed no significant difference. Conclusion: The type of lesion found mostly were erosion and hyperemic. The most frequent location was gaster.